2004
DOI: 10.1530/eje.0.1510771
|View full text |Cite
|
Sign up to set email alerts
|

Multiple endocrine neoplasia 2A syndrome presenting as peripartum cardiomyopathy due to catecholamine excess

Abstract: We report the case of a 24-year-old female with a history of medullary thyroid carcinoma who presented at 38 weeks gestation with acute chest pain and shortness of breath. She was found to be in pulmonary edema and respiratory failure. An emergency cesarean section was performed. Subsequently, an echocardiogram revealed an ejection fraction of 10%. After medical therapy with digoxin, milrinone, captopril and diuretics, her condition improved rapidly and a repeat echocardiogram showed that the left ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 33 publications
(42 reference statements)
0
24
0
Order By: Relevance
“…The reversibility of the cardiomyopathy in pheochromocytoma indicates that it is catecholamine induced, and removal of the adrenal mass can lead to resolution of the cardiomyopathy. 8 The effects of catecholamines in pregnancy were demonstrated when dobutamine, a sympathomimetic agent, produced a reduction of contractile cardiac reserve and suboptimal response to hemodynamic stresses. 26 This study demonstrated that patients with previous cardiomyopathy during pregnancy and seemingly normal cardiac function after delivery showed decreased cardiac reserve when treated with an amount of dobutamine that normally would mimic the increased cardiac output of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The reversibility of the cardiomyopathy in pheochromocytoma indicates that it is catecholamine induced, and removal of the adrenal mass can lead to resolution of the cardiomyopathy. 8 The effects of catecholamines in pregnancy were demonstrated when dobutamine, a sympathomimetic agent, produced a reduction of contractile cardiac reserve and suboptimal response to hemodynamic stresses. 26 This study demonstrated that patients with previous cardiomyopathy during pregnancy and seemingly normal cardiac function after delivery showed decreased cardiac reserve when treated with an amount of dobutamine that normally would mimic the increased cardiac output of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, the patient may present with non-cardiac pulmonary edema or aortic dissection (26)(27)(28). Patients who develop unexplained peripartum cardiomyopathy should also be examined for the existence of a pheochromocytoma (29)(30)(31). The initially reported high maternal mortality in undiagnosed and untreated patients was as high as 50% (5,6,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been associated with the development of dilated cardiomyopathy, myocarditis, and heart failure. [1][2][3][4][5][6][7][8][9][10][11] Pheochromocytoma as a cause of systemic hypertension occurs in less than 1% of hypertensive patients. Surgical removal is curative in greater than 85% of cases.…”
Section: Discussionmentioning
confidence: 99%